Dispelling the myths around the role of a general practice nurse. (2nd August 2022) - Butler, Sarah
Abstract : There are many myths surrounding the general practice nurse role. Sarah Butler looks at these myths and clears up some of the misunderstandings that are often repeated In the UK there is a need to promote and increase the number of general practice nurses working in primary care. In comparison to their counterparts in secondary care, practice nurse numbers are significantly reduced. In recent years emphasis was placed on keeping individuals well and out of hospital and their conditions managed in primary care where possible. The role of the general practice nurse is still lesser known compared to the role of a staff nurse. Myths still remain around the general practice nurse position including those eligible to apply and the development that is offered.